HUBUNGAN PENGETAHUAN DENGAN SIKAP PENGGUNAAN TABLET Fe PADA WANITA DALAM PENCEGAHAN STUNTING DI RW 012 DESA SUKAMEKAR - Suryanih, Anisa; Yanti, Silfera Indra; Shoaliha, Maratun (Universitas Imelda Medan, 2024)
Iron or Fe deficiency is still a micronutrient problem in the world, especially in Indonesia. The cause of iron deficiency is lack of knowledge and unsupportive attitudes. The aim of the research is to determine the relationship between the level of knowledge and attitudes towards using Fe tablets among women in preventing stunting in RW 012 Sukamekar Village. The research uses an analytical survey method through a cross sectional approach, namely collecting data all at once or at one time. The data collection technique is through distributing questionnaires, the technique used to determine the sample in this research is Non Random Sampling, using a Purposive sampling technique. The results of this research from 75 respondents showed knowledge of the use of Fe tablets in women in preventing stunting in RW 012 Sukamekar Village, 30 (40%) had sufficient knowledge, 29 (38.7%) people had a good attitude. Bivariate analysis obtained a p value of 0.024 (<p=0.005). The conclusion from this research is that there is a relationship between knowledge and attitudes towards using Fe tablets among women in preventing stunting in RW 012 Sukamekar Village with a p-value of 0.024.